(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Multi-system Inflammatory Syndrome in Children (MIS-C) is an extremely rare but dangerous hyper-inflammatory disease linked to COVID-19 infection that results in fever, gastrointestinal and skin/mucous membrane symptoms and is also accompanied by cardiovascular issues such as shock and myocarditis.[1,2] Below are the demographic data, clinical manifestations, treatments and clinical outcomes of the children diagnosed with MIS-C who were admitted to our tertiary hospital. Materials and Methods: The medical files of all children under the age of 18 who met the World Health Organization (WHO) criteria for MIS-C admitted at our tertiary hospital between 2020–2021 were retrospectively examined. Information regarding demographics, clinical manifestations, laboratory and echocardiographic tests, treatments and clinical outcomes were collected from the files. Statistical analysis was performed with SPSS version 20. Differences among categorical variables were calculated with the chi-square (χ²) test or Fisher’s exact test and differences among continuous variables were tested with Student t- tests or Mann-Whitney U tests. Because of the number of statistical tests, a Bonferonni adjustment for multiple comparisons was made. Results: A total of forty patients (62.5% males) were evaluated (mean age 8.16 ± 2.62 years). Most patients (nearly 90%) experienced fever, and gastrointestinal symptoms (e.g., abdominal pain, vomiting, diarrhea). Commonly observed mucocutaneous signs (e.g., rash = 50%, oral changes = 45%, conjunctivitis = 47.5%) and lymphadenopathy occurred commonly. Eight patients (20%) developed shock (cardiogenic/vasoplegic), and nine patients (22.5%) developed myocarditis. The mean ages of patients developing shock and myocarditis did not differ (p > 0.05). However, patients with shock had higher levels of cardiac troponin and N-terminal pro b-type natriuretic peptide (NT-proBNP) than non-shock patients (mean troponin level 1.04 vs. 0.12 ng/mL, p = 0.003). Echocardiographic abnormalities were present in 47.5% of the patients overall; six (15%) patients had coronary artery dilation or ectasia. Eleven patients (27.5%) required inotropic support and three (7.5%) patients required mechanical ventilation. Intensive care unit admission was necessary for seventeen (42.5%) patients. Immunotherapy was universally administered: 95% received aspirin, 50% received intravenous immunoglobulin (IVIG), and 75% received corticosteroids (37.5% were given pulse dose steroids). Thirty percent of the patients received both IVIG and steroid therapy. Patients who developed shock were more likely to have been treated with IVIG (100% vs. 37.5%, p = 0.006) and with combined IVIG and steroid therapy (87.5% vs. 15.6%, p < 0.001). One patient (2.5%) died (in the shock group). At 6 weeks all 39 discharged patients were clinically stable with improvement on echocardiography; 34 completed 3- and 6-month follow-up and had no residual echocardiographic changes. One child had permanent neurological sequelae from hypoxic brain injury. Conclusion: In this study, most of the children who had MIS-C presented with fever, gastrointestinal and mucocutaneous symptoms, and approximately one fifth of them developed shock. Cardiac injury biomarkers were substantially higher in patients with shock, indicating cardiac damage. Therefore, we believe that when these children are identified early as having shock and myocardial dysfunction, aggressive immunomodulatory therapy should be initiated. With timely immunomodulatory treatment, immediate and 6-month outcomes were favorable for most children; however, rare severe neurological sequelae can occur.